2021
DOI: 10.37291/2717638x.202123117
|View full text |Cite
|
Sign up to set email alerts
|

“How will you construct a pathway system?”: Microanalysis of teacher-child scientific conversations

Abstract: During the preschool years, children’s question-explanation exchanges with teachers serve as a powerful mechanism for their early STEM knowledge acquisition. Utilizing naturalistic longitudinal classroom data, we examined how such conversations in an inquiry-based preschool classroom change during an extended scientific inquiry unit. We were particularly interested in information-seeking questions (causal, e.g. “How will you construct a pathway?”; fact-based, e.g., “Where’s the marble?”). Videos (n = 18; 14 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…It is consistent with constructivist learning theories that children learn best when they engage actively in learning. Children's information‐seeking questions occur in the sustained shared thinking process, which allows them to construct increasingly complex knowledge based on prior experiences, driven by curiosity and motivation (Haber et al, 2021). Therefore, the intellectual aspects of teacher–child interaction — such as problem‐solving, concept clarification, activity evaluation, or narrative extension in supporting learning and critical thinking — might have the most promising links to positive child outcomes than other aspects of interaction.…”
Section: Discussionmentioning
confidence: 99%
“…It is consistent with constructivist learning theories that children learn best when they engage actively in learning. Children's information‐seeking questions occur in the sustained shared thinking process, which allows them to construct increasingly complex knowledge based on prior experiences, driven by curiosity and motivation (Haber et al, 2021). Therefore, the intellectual aspects of teacher–child interaction — such as problem‐solving, concept clarification, activity evaluation, or narrative extension in supporting learning and critical thinking — might have the most promising links to positive child outcomes than other aspects of interaction.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, there were 3 articles published [15], [32], [33]. In 2021, there were 6 articles published [34]- [39]. The year 2022 saw the highest number of publications with 7 articles [16], [20], [40]- [44].…”
Section: Years Of Publicationmentioning
confidence: 99%
“…Regarding the geographical distribution, as illustrated in Figure 3, the included articles were conducted in various countries. The United States [29]- [31], [34], [44], Türkiye [15], [16], [40], [43] were the two countries with the highest number of articles included. Additionally, studies were conducted in Italy [33], England [35], [38], [42], Finland [36], Sweden [37], Spain [39], Switzerland [41], Australia [20], Jordan [32].…”
Section: Research Locationsmentioning
confidence: 99%
“…Few studies have examined children's questions during teacher-child science discussions in the classroom. (e.g., Haber, Leech, et al, 2021;Haber, Puttre, et al, 2021;Kurkul et al, 2021). These reports have found that children ask challenging questions about scientific and nature-related topics, religion, sex and reproduction, and everyday life in the classroom (Sak, 2019).…”
Section: Teachers As Informants and Teacher-child Conversationsmentioning
confidence: 99%
“…Other surveys have also found that teachers were more likely to provide explanations for children's scientific questions (Haber, Leech, et al, 2021). Studies of actual teacher-child interactions have found that children were more likely to ask causal questions first and factbased questions later (Haber, Puttre, et al, 2021). Although these studies are informative, more studies are needed to examine children's questions within teacher-child interactions at schools, especially with respect to specific topics, such as the COVID-19 pandemic.…”
Section: Teachers As Informants and Teacher-child Conversationsmentioning
confidence: 99%